2019
DOI: 10.1097/md.0000000000014463
|View full text |Cite
|
Sign up to set email alerts
|

Oral glutamine supplements reduce concurrent chemoradiotherapy-induced esophagitis in patients with advanced non-small cell lung cancer

Abstract: Background: Complications related to concurrent chemoradiotherapy (CCRT) such as acute radiation-induced esophagitis (ARIE) may cause significant morbidity and unplanned treatment delays in patients with advanced non-small cell lung cancer (NSCLC). We designed a prospective randomized study to assess the impact of glutamine (GLN) supplementation in preventing CCRT-induced toxicities of advanced NSCLC patients. Methods: From September 2014 to September 2015, 60 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Non‐small cell lung cancer (NSCLC) is one of the most malignant tumors with the fastest growth rate of morbidity and mortality in the world (Balata et al, 2019; Chang et al, 2019). The primary treatment of NSCLC includes surgery, radiotherapy, chemotherapy, targeted therapy, and immunotherapy (Dafni et al, 2019; Wan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Non‐small cell lung cancer (NSCLC) is one of the most malignant tumors with the fastest growth rate of morbidity and mortality in the world (Balata et al, 2019; Chang et al, 2019). The primary treatment of NSCLC includes surgery, radiotherapy, chemotherapy, targeted therapy, and immunotherapy (Dafni et al, 2019; Wan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, glutamine may play an important role in glutathione synthesis, which can decrease the oxidative stress (42). Several clinical studies (43,44) also established the effects of oral glutamine in preventing and treating cancer treatment related injuries. Chang and colleagues (43) found a beneficial effect of oral glutamine supplementation for the prevention from radiation-induced esophagitis in advanced patients with advanced non-small cell lung cancer who undergoing concurrent chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies (43,44) also established the effects of oral glutamine in preventing and treating cancer treatment related injuries. Chang and colleagues (43) found a beneficial effect of oral glutamine supplementation for the prevention from radiation-induced esophagitis in advanced patients with advanced non-small cell lung cancer who undergoing concurrent chemoradiotherapy. Randomized trial performed by Eda et al (44) suggested that enteral glutamine minimizes radiation induced dermatitis in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the etiology of chemotherapy-induced mucositis can be divided into two main causes. One primary cause is mucosal inflammation due to the destruction of the cells caused by reactive oxygen species (superoxide or hydroxy radicals) generated by anticancer agents [ 4 , 5 ]. Cells in the oral mucosa also will be exposed to metabolic damage as a result of their uptake of anticancer agents, ends up in blocking healthy oral mucosal cell turnover.…”
Section: Introductionmentioning
confidence: 99%